KAMPANYE LINTAS BUDAYA UNTUK MENGURANGI TINGKAT STRES PADA MAHASISWA PARUH WAKTU DI INGGRIS - Athaya Zahra (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2019)
Contrary to numbers of labour markets in England, which have been increased presently, the mental health issue regarding work stress has become more threatening in the past fve years. Surprisingly, the dominant group is young ages between 18-29-years-old, particularly full-time students who have a part-time job or work. This circumstance is unfortunate, given the fact that young people are likely to be the key to drive the industry innovation forward. However, the core problem of this matter is current stress relief method that has been provided by a company or institution is probably less relevant to student’s culture and demands. In-depth research was conducted through secondary and primary studies, such as literature analysis; observation of DMU Mental Health Day event; online questionnaire of 50 DMU students; an interview with DMU Employability and Wellbeing staﬀ; interviews with 3 DMU Britain students, and a focus group involving East Asia students. As a result, key fndings were revealed, including: 1) 40 out of 44 DMU full-time students who have part-time job felt stressed due to working; 2) what young people need the most when they were stressed was a short break; 3) East Asia cultures have certain treatments which helped students to get relaxed; 4) students showed less interest in joining stress management services provided by the University and preferred to resolve the problem individually due to the fact that students believe it was their personal. Through this study, ESCAPE15, a social campaign prototype was designed to examine the eﬀectiveness of East Asian relief method in order to alleviate part-time student’s stres in England.